2019
DOI: 10.1093/europace/euz142
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-isolation-guided cryoballoon ablation reduces oesophageal and mediastinal alterations detected by endoscopic ultrasound: results of the MADE-PVI trial

Abstract: Aims Cryoballoon ablation is safe and efficient for achieving pulmonary vein isolation (PVI) in atrial fibrillation. Structural oesophago-mediastinal lesions, which seem to be associated with an increased risk of the lethal complication of an atrio-oesophageal fistula, have been described. MADE-PVI (Mediastino-oesophageal Alterations Detected by Endosonography after PVI) aimed at evaluating safety of cryoballoon PVI in relation to two different freeze protocols. As time-to-isolation-(TTI)-gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…The MADE-PVI trial. The design and results of the MADE-PVI study have been reported in detail 6 . In brief, MADE-PVI was a prospective, controlled single-centre trial and conducted to investigate whether the ablation strategy employing 2nd generation cryoballoon had an impact on the occurrence of oesophageal and mediastinal lesions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MADE-PVI trial. The design and results of the MADE-PVI study have been reported in detail 6 . In brief, MADE-PVI was a prospective, controlled single-centre trial and conducted to investigate whether the ablation strategy employing 2nd generation cryoballoon had an impact on the occurrence of oesophageal and mediastinal lesions.…”
Section: Methodsmentioning
confidence: 99%
“…In all patients, cryoballoon PVI was performed as described elsewhere in detail 6 . Two different ablation strategies were pursued: either a conventional protocol which consisted of 2 × 180 s freezes or a TTI-guided ablation protocol were employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all groups, the catheter setup was complemented by a decapolar coronary sinus catheter and a quadripolar catheter that was positioned in the right ventricle. After ablation, protone pump‐inhibitors were added to the medication of every patient for 4 weeks after ablation to prevent esophageal damage associated to ablation 8‐10 …”
Section: Methodsmentioning
confidence: 99%
“…Our previous study suggested that modified ablation guided by esophageal visualization could decrease the occurrence of EI and there was no significant difference in AF recurrence during 12-month follow-up 10 . www.nature.com/scientificreports www.nature.com/scientificreports/ The latest study indicated that cryoballoon ablation for AF guided by time to PVI reduced the esophageal complications 19 . Consistent with the previous survey on cryoballoon ablation, in which a total of 11 cases of AEF were reported from more than 120,000 cases worldwide 20 , our data supported that cryoballoon ablation had lower incidence of EI, although this is not our main aim.…”
Section: Incidence and Predictors Of Esophageal Injurymentioning
confidence: 99%